THE LEGALITY OF DIVORCE IN THE PERSPECTIVE OF HADITH - Ridwan Hasbi; Syafaruddin Hasbi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Cerai talak (formula for divorce) and Cerai gugat (sue for divorce) are two terms of termination of marriage bond in Indonesia. The formula of divorce is a term that coincides with a divorce coming from the will of a husband and sue for divorce is the desire of a wife to separate from her husband. Islamic Law legalizes the right of wives in cases of divorce redeem (khulu‘) and fasakh because of syiqaq. On the other side, there are signs setting the rights up, so that the given reasons to use the rights must be legal in syar‘i. The reasons for the legality of divorce is a common-cause factor, so that the banning with threatening hadiths as well as those of the hadiths that say wives must obey their husbands, the wives should not hurt their husband and the wives are prisoners of husbands are all categorized into general. At another angle, there also the hadiths concerning with the status a couple husband and wife is heaven and hell for them in a household. Contextualization of hadiths that ban a wife asking for divorce without any legal cause from Syar‘i, and also those of the hadiths legalize khulu‘ are the realization of the conjugal lives with regards to the mandate of Allah and religious values. The facts of a wife sue for divorce to her husband are the conditions related to a confusion occurred in a household which are influenced by a variety of factors, i.g. economy, adultery, polygamy, social strata and others. A sue for divorce which is Syar’i based condition is a disagreement prolonged strife after peace held between the two sides and act endangers a wife